Effect of Hypnopressure on Anxiety in Pregnant Women with Preeclampsia - Riska Ismawati Hakim; Suharyo Hadisaputro; Suhartono Suhartono; Runjati Runjati (Universitas Muhammadiyah Semarang, 2022)
Background: Preeclampsia in pregnancy is one of the dominant causes of maternal death in the world and will be seven times higher in developing countries. Anxiety is more common in pregnant women with preeclampsia than normal pregnant women and will aggravate that condition. Hypnotherapy can reduce anxiety and blood pressure, but not all pregnant women are easily suggested and show resistance to hypnotherapy. Objective: This study aims to prove the effect of hypnopressure on anxiety in pregnant women with preeclampsia. Methods: This study used queasy-experimental with pretest-postest design on two groups of study. Hypnopressure was a stimulation technique at yintang, neiguan and baihui points during hypnotherapy. It was applied one hour weekly for three weeks in intervention group, while the control group received integrated ANC as standard care and anti-hypertension. A consecutive sampling was conducted for 40 pregnant women with preeclampsia and divided into two groups or 20 women for each group. Instruments used to measure anxiety applied Zung Self-Rating Anxiety Scale (ZSAS). Data analysis used paired and independent t-test. Results: After the intervention of hypnopressure, anxiety score decreased significantly from 44.90 to 33.75 with p-value <0.001. In the control group, anxiety score was reduced form 45.65 to 42.70 with p-value <0.001. Hypnopressure could reduce anxiety score greater than control group. Conclusion: Hypnopressure has the effect of reducing anxiety levels in pregnant women with preeclampsia.